Pré-condicionamento nutracêutico com misturas de óleos Ômega 3, 6 e 9 para atenuar as características neuroinflamatórias do transtorno do espectro autista Induzidas pelo ácido valpróico em um modelo animal - Ribeiro, Luciana Fujiwara Aguiar (2020)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder with abnormalities in the immune system, metabolism and behavioral functions. Over the past 15 years, great interest has been given to the potential role of Omega-3 polyunsaturated fatty acids to understand the pathogenesis of some diseases and to treat neurodevelopmental and psychiatric disorders. In the present study, mixtures of omega 3, 6, and 9 oils with different types of Omega-3 were used according to their structural characteristics: Mix-1 (linolenic fatty acid – ALA), Mix-2 (ALA – 35%) + eicosapentaenoic fatty acid (EPA – 39%) + fatty acid docosahexaenoic acid (DHA – 26%) and Mix-3 (ALA – 84%; DHA – 16%) to evaluate their neuroinflammatory and antioxidant effects in the animals’ behavior, as well as the gene expression in male and female Wistar rats submitted to ASD induction with a single dose of valproic acid (VPA) sc 400mg/kg on the 14th day after birth. The oil mixes were administered by gavage for 25 days continuously starting on the 15th day of birth; water and ration were made available ad libitum. Then, behavioral tests were performed - open field; tail immersion; swimming performance and rotarod. On the 55th day after birth, four brain areas (hippocampus, prefrontal cortex, amygdalae and cerebellum) were dissected to determine the degree of lipid peroxidation, nitrite concentration and glutathione reductase levels. Additionally, the hippocampus gene expression of the control 0.9% saline, VPA, Mix-3 and Mix-3 + VPA groups was evaluated using the Dnmt3a and Achd2 genes. Both in male and female groups VPA showed a significant increase in latency compared to saline, improving their pain response after treatment with Mix-1, Mix 2 and Mix-3 in the VPA groups. Deficit in motor skills integration was noted in swimming performance in VPA groups of both sexes. In locomotor activity, only the females of the VPA group suffered a significant reduction, where once again the mixes rich in Omega-3 (Mix-1 and Mix-2) were able to restore their locomotor activity. A significant increase in oxidative stress occurred in the hippocampus and prefrontal cortex in males, being reduced with the action of Mix-2 and Mix -3 in the VPA groups. No antioxidant response from glutathione reductase was observed in this study. A high production of NO nitric oxide was noted in the cerebellum of the VPA group of male animals, which may represent a consequence of inflammatory process. Treatment with VPA in males did not represent a significant increase in gene expression for the hippocampal area of the Dnmt3a and Achd2 genes. Our findings suggest that the mixture of oils rich in omega- 3 was favorable to the reduction of oxidative stress (Mix-2 and Mix-3) and effects in reducing behavioral alterations of ASD in rats.